Perspektif Guru dan Siswa SMKS Fania Salsabila Kota Jambi tentang urgensi pembelajaran hukum ketenagakerjaan untuk membangun entrepreneurship Alumni - Rafindo, Yanuar; Salam, M; Dewi, Nurmalia; Yetniwati, Yetniwati (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This research aims to find out the perspective of teachers and students of Fania Salsabila Vocational School, Jambi City regarding the urgency of learning employment law to develop entrepreneurship alumni. To find out the importance of your rights and obligations as a worker, then regarding existing employment laws. This research was conducted at Fania Salsabila Vocational School, Jambi City. Research data was obtained by observing, interviewing and documenting teachers, students and the head of the Jambi Province official vocational school assessment curriculum section. The informants used as subjects included: 2 teachers, 3 students and 1 Jambi provincial office. The approach used is a descriptive qualitative approach with descriptive qualitative research type narrative research. The research results can be concluded that the perspective of vocational school teachers and students regarding the urgency of learning labor law is that teachers and students do not know enough, understand labor law but know it is important and agree that learning labor law is important. From the results of this research, it is recommended that teachers and students work together to realize labor law learning in the curriculum and vocational high schools.